Chulanova G. V., Shevchenko S. V. Gender marked words in advertising texts: the equivalence of translation - Chulanova G. V.; Shevchenko S. V. (Philological Treatises, 2020)
The article deals with the peculiarities of translation of English advertising texts with gender markedness which is reflected through the usage of the gender marked words. The paper is aimed at the distinguishing the characteristic features of the process of translation of advertising texts containing gender marked units. The aim of the research implies the conducting of the detailed analysis of the advertising text as a linguistic phenomenon and the nature of the gender marked units as an effective means for influencing the addressee in the process of advertising communication. The main categories of the gender marked units within advertising texts were defined. The influence of the defined types of gender markedness of the advertising texts on the process of their translation was also analyzed